2022
DOI: 10.3389/fped.2022.894589
|View full text |Cite
|
Sign up to set email alerts
|

Italian Version of the Cornell Assessment of Pediatric Delirium: Evaluation of the Scale Reliability and Ability to Detect Delirium Compared to Pediatric Intensive Care Unit Physicians Clinical Evaluation

Abstract: BackgroundDelirium is an acute brain dysfunction associated with increased length of hospitalization, mortality, and high healthcare costs especially in patients admitted to the pediatric intensive care unit (PICU). The Cornell Assessment of Pediatric Delirium (CAPD) is a screening tool for evaluating delirium in pediatric patients. This tool has already been used and validated in other languages but not in Italian.ObjectivesTo test the reliability of the Italian version of the CAPD to screen PICU patients for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…These estimates imply that kappa in children less than 2 years old was less than 0.6. A study examining IRR of the Italian version of the CAP-D found an excellent ICC of 0.93 (95% CI 0.89–0.96); however, the type of ICC was not reported, thus significantly limiting interpretability of the results (17, 20). A study examining validity of CAP-D in children older than 6 months old found slight to moderate agreement between bedside nurse and reference standard, with kappa of 0.4 (95% CI 0.26–0.54) and an increased likelihood of discordant results when patients were younger (odds ratio [OR] = 1.1; 95% CI 1–1.2) and received any sedation ([OR = 4.1; 95% CI 1.5–11.5) (10).…”
Section: Discussionmentioning
confidence: 99%
“…These estimates imply that kappa in children less than 2 years old was less than 0.6. A study examining IRR of the Italian version of the CAP-D found an excellent ICC of 0.93 (95% CI 0.89–0.96); however, the type of ICC was not reported, thus significantly limiting interpretability of the results (17, 20). A study examining validity of CAP-D in children older than 6 months old found slight to moderate agreement between bedside nurse and reference standard, with kappa of 0.4 (95% CI 0.26–0.54) and an increased likelihood of discordant results when patients were younger (odds ratio [OR] = 1.1; 95% CI 1–1.2) and received any sedation ([OR = 4.1; 95% CI 1.5–11.5) (10).…”
Section: Discussionmentioning
confidence: 99%
“…The ICC values were interpreted as indicated by Koo and Li (2016) : ICC < 0.5 indicated poor reliability, ICC between 0.5 and 0.75 indicated moderate reliability, ICC between 0.76 and 0.90 indicated good reliability, and ICC > 0.90 indicated excellent reliability. The ICC method for assessing reliability has been employed similarly in previous studies evaluating the reliability of the CAPD [ 24 , 34 ]. Additionally, a Bland-Altman plot was included to enhance understanding of inter-rater reliability.…”
Section: Methodsmentioning
confidence: 99%